Superposition principle in bridge aerodynamics: Modelling of self-excited forces for bridge decks in random vibrations. (15th January 2019) - Siedziako, Bartosz; Øiseth, Ole
Highlights: A validity of the Principle of Superposition for the self-excited forces is examined. 18 aerodynamic derivatives are identified at two reduced velocities simultaneously. The self-excited forces measured during execution of random motions are examined. Abstract: The modeling of self-excited forces in modern bridge aerodynamics traditionally involves the assumption of superposition. The use of a linear load model allows to perform sophisticated buffeting analyses, where the response consists of multiple frequency components, even though the aerodynamic derivatives have been determined by single harmonic forced vibration test. The principle of superposition is also of crucial importance when assessing the critical flutter velocity, since the flutter motion is dissimilar to the motion considered in the standard wind tunnel tests. In this study, a recently-developed forced vibration setup that can force arbitrary motions is used to examine the linearity of the load model for self-excited forces considering several frequency components. The section model is first forced into bi-harmonic motions to be able to determine the aerodynamic derivatives for two different reduced velocities at the time. The results correspond in an excellent manner to aerodynamic derivatives from standard forced vibration tests. Further, the aeroelastic forces are measured during broad-banded motions and compared in time and frequency domains with self-excited forces predicted using rational functions. The experimental results confirm that the principle of superposition is valid for lift and pitch for the wedged-shape box cross-section considered. Significant nonlinearities are, however, observed for the self-excited drag, which implies that the principle of superposition does not apply.